Consumer Expenditure Survey, 1985: Diary Survey ([Verlag nicht ermittelbar], 1988)
The ongoing Consumer Expenditure Survey (CES) provides a continuous, comprehensive flow of data on the buying habits of American consumers. In addition, these data are employed to maintain and to review the Consumer Price Index. The Diary, or recordkeeping, component of the CES contains expenditure data for items purchased on a daily or weekly basis. Participants from consumer units, which are roughly equivalent to households, are asked to maintain expense records, or diaries, of all purchases made each day for two consecutive one-week periods. Diaries are designed to record information on small, frequently purchased items such as food, beverages, food consumed away from home, gasoline, housekeeping supplies, nonprescription drugs and medical supplies, and personal care products and services. Information is also elicited at the end of the two-week period on work experience, occupation, industry, retirement status, member earnings from wages and salaries, net income from business or profession, net income from one's own farm, and income from other sources.